Synthetic Review of Organizational learning - Turi, Jamshid Ali (Advances in Social Sciences Research Journal, 2019)
This paper covers comprehensive literature analysis on organizational learning. Work on organizational learning was synthesised in systematic and chronological order. Cognitive, Social and Behavioural theories and factors in organizational context have been widely discussed to comprehend forgetting in organizational context. Moreover, historical and philosophical prospective of organization learning was also comprehended. All the theories, prevailing context and factors indicate, as evident from content analysis, have greater impact on organizational learning.